2016
DOI: 10.18632/oncotarget.7900
|View full text |Cite
|
Sign up to set email alerts
|

Response of brain metastasis from lung cancer patients to an oral nutraceutical product containing silibinin

Abstract: Despite multimodal treatment approaches, the prognosis of brain metastases (BM) from non-small cell lung cancer (NSCLC) remains poor. Untreated patients with BM have a median survival of about 1 month, with almost all patients dying from neurological causes. We herein present the first report describing the response of BM from NSCLC patients to an oral nutraceutical product containing silibinin, a flavonoid extracted from the seeds of the milk thistle. We present evidence of how the use of the silibinin-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…Accumulating evidences show that silibinin, a classical anti-fibrosis drug, exhibits strong anti-cancer activity in several human malignant tumors ( Wu et al, 2013 ; Bosch-Barrera et al, 2016 ), but the underlying mechanism is still unknown. In consideration of one important molecule during fibrosis is LOX in hepatocyte, we suspected that whether the EGFR/LOX pathway plays a role in its anti-metastasis effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidences show that silibinin, a classical anti-fibrosis drug, exhibits strong anti-cancer activity in several human malignant tumors ( Wu et al, 2013 ; Bosch-Barrera et al, 2016 ), but the underlying mechanism is still unknown. In consideration of one important molecule during fibrosis is LOX in hepatocyte, we suspected that whether the EGFR/LOX pathway plays a role in its anti-metastasis effect.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, silibinin induces cancer cell cycle arrest ( Feng et al, 2015 ), apoptosis ( Zhang et al, 2015 ), inhibits tumor energy metabolism ( Raina et al, 2013 ), significantly inhibits tumor metastasis ( Bosch-Barrera and Menendez, 2015 ; Jiang C. et al, 2016 ). Importantly, Menendez’s study showed that lung cancer patients treated with silibinin had significantly inhibited brain metastasis in clinical ( Bosch-Barrera et al, 2016 ). Silibinin also showed a therapeutic effect on bladder cancers ( Wu et al, 2013 ), breast cancers ( Kim et al, 2016 ), prostate cancers ( Deep et al, 2014 ), liver cancers ( Polachi et al, 2016 ), etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also find that, in hematological disorders, silibinin also can suppress the activation of some pathways, such as NPM-ALK, and then suppress its key downstream pSTAT3 [ 28 ]. It is noteworthy that, silibinin still have some limitation of clinical use: One of the biggest limitations in humans is its low oral bioavailability [ 41 ]. This forces us to seek new formulations.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Silibinin has been shown to have significant anti-cancer effects in a variety of cancer types [ 1 ], including prostate [ 1 3 ], bladder [ 4 , 5 ], kidney [ 6 , 7 ], skin [ 8 , 9 ], pancreas [ 10 ], breast [ 3 , 11 ], lung [ 12 14 ] and colon [ 15 , 16 ] cancers. Silibinin is also effective in inhibiting brain metastases from non-small cell lung cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%